Grundschulforschung braucht Transfer: Brückenschläge zur Lehrkräftebildung, Bildungspolitik und Schulpraxis. Beitrag auf der 33. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der PH Vorarlberg, Österreich. - Büker, Petra

Demokratie kann man lernen (Die Grundschulzeitschrift Jahresheft)

The Question of Methodology in Critical Political Economy of Communication and the Media - Fuchs, Christian (Journal of Communication Inquiry)
Critical political economy of communication and the media (CPECM) is an approach and field of study that critically analyzes how the interaction of politics and the economy in society shapes and is shaped by (mediated) communication. This study asks: What is the role of methodology in the approach of CPECM? How are methods and media ethics related in the critical study of media, economy, and society? The article argues that CPECM is distinct in that it asks special types of questions that are different from the questions asked by administrative research. This study points out 10 methodological dimensions of CPECM. It argues that empirical ideology critique should not be situated outside but inside of CPECM. It becomes evident that, other than conventional methods in media and communication studies, CPECM methodology is guided by ethics, moral philosophy, and critical theories.

DigiLex — A Checklist for the Evaluation of Digital Tools for Second and Foreign Language Lexical Learning - Lehmkuhl, Paulina; Wagner, Benedikt; Frisch, Stefanie; Rumlich, Dominik; Visser, Judith (TESOL Journal)
ABSTRACT The use of digital tools for second and foreign language lexical learning is increasingly popular and research in this area is constantly expanding. However, little has been written about specific criteria that could be used to identify tools with high‐quality lexical input, as available checklists and frameworks for digital media tend to neglect detailed analyses of the vocabulary domain. This article addresses this issue by presenting the Checklist for Evaluating Digital Resources for Lexical Learning (DigiLex), which combines important digital language learning criteria with an extensive evaluation of lexical content. The checklist is both theory‐based and user‐friendly, aiming to fill a gap between theory and practice in the field of digital lexical learning. The article discusses the theoretical basis of the checklist and integrates the results of a small pilot study with pre‐service and in‐service teachers, emphasizing feasibility in everyday learning and teaching. By providing an easy‐to‐use tool for identifying suitable digital resources, the DigiLex checklist aims to support language learners and teachers in self‐regulated lexical learning.

Kompetenzen für den erfolgreichen Übergang von der Sekundarstufe I in die berufliche Ausbildung sichern. Gutachten der Ständigen Wissenschaftlichen Kommission der Kultusministerkonferenz - Becker-Mrotzek, Michael; Efing, Christian; Gerick, Julia; Greefrath, Gilbert; Hammann, Marcus; Hannover, Bettina; Heckhausen, Jutta; Jost, Jörg; Keller, Stefan; Leiß, Dominik; Leutner, Detlev; Lewalter, Doris; et al.

Maximizing linguistic and cognitive potential: the role of vocal training with pop songs in teaching English as a foreign language - Vivone, Antonio; Rumlich, Dominik; Lehmann-Wermser, Andreas (Learning: Research and Practice)

High Voltage (5Vpp) Driver Monolithically Integrated with Thermally Tunable Optical Ring Resonators in a Silicon Photonics Technology - Weizel, Maxim; Gudyriev, Sergiy; Zazzi, Andrea; Müller, Juliana; Schwabe, Tobias; Witzens, Jeremy; Scheytt, J. Christoph (2025 32nd IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Analogiebildung in kontextorientierten Lernumgebungen - Wedekind, Lisa; Pollmeier, Pascal; Fechner, Sabine (Entdecken, lehren und forschen im Schülerlabor)

CLIL-related benefits for general EFL proficiency - Rumlich, Dominik (The Cambridge Handbook of multilingual education)

Inspirationspapier: Digitale Kompetenzen fördern, Digital Divide überwinden – Was wir von Tschechien lernen können - Eickelmann, Birgit; Puchta, J.; Thieme, L.; Zöller, K.

Explainable Benchmarking through the Lense of Concept Learning - Zhang, Quannian; Röder, Michael; Srivastava, Nikit; Kouagou, N'Dah Jean; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference 2025)

Jakob Wüest: Une histoire des connecteurs logiques. Causalité, argumentation, conséquence, finalité et concession. Tübingen: Narr / Francke / Attempto 2023, 319 S. (Tübinger Beiträge zur Linguistik, 586) - Kunert, Irene Dorothea (Romanische Forschungen)

Predetection squeezing as a resource for high-dimensional Bell-state measurements - Bianchi, Luca; Marconi, Carlo; Sperling, Jan; Bacco, Davide (Physical Review Research)
Bell measurements, entailing the projection onto one of the Bell states, play a key role in quantum information and communication, where the outcome of a variety of protocols crucially depends on the success probability of such measurements. Although in the case of qubit systems, Bell measurements can be implemented using only linear optical components, the same result is no longer true for qudits, where at least the use of ancillary photons is required. In order to circumvent this limitation, one possibility is to introduce nonlinear effects. In this work, we adopt the latter approach and propose a scalable Bell measurement scheme for high-dimensional states, exploiting multiple squeezer devices applied to a linear optical circuit for discriminating the different Bell states. Our approach does not require ancillary photons, is not limited by the dimension of the quantum states, and is experimentally scalable, thus paving the way toward the realization of an effective high-dimensional Bell measurement.

Sportsoziologie - Riedl, Lars (Sportwissenschaft. Themenfelder, Theorien und Methoden)

Identifizierung und Entwicklung von tragfähigen Geschäftsmodellen für Kulturplattformen im Datenraum Kultur - Vorbohle, Christian; Althaus, Maike; Kundisch, Dennis

Sponsoring als Geschäftsmodell für Kulturplattformen im Datenraum Kultur: Vorstellung und Validierung - Vorbohle, Christian; Althaus, Maike; Kundisch, Dennis

Kulturplattformen im Datenraum Kultur: Eine Analyse bestehender Geschäftsmodelle von Kulturplattformen - Althaus, Maike; Vorbohle, Christian; Kundisch, Dennis

Modifizierter Torsionsversuch zur Untersuchung des Tragverhaltens von Clinchpunktmehrfachanordnungen - Lüder, Stephan; Wolf, Eugen; Brosius, Alexander; Schmale, Hans Christian (43. Vortrags- und Diskussionstagung Werkstoffprüfung 2025)
Zur Prüfung der mechanischen Eigenschaften von mechanisch gefügten Verbindungen wird gemäß der Normung in der Regel nur ein Fügepunkt verwendet. In diesem Beitrag wird die Prüfung von Mehrfachanordnungen von Clinchpunkten in einem modifizierten Torsionsversuch beschrieben. Bei den Fügeverbindungen der Proben aus artgleichen Werkstoffen handelt es sich um zwei Varianten symmetrischer Mehrfachanordnungen von vier Clinchpunkten mit zwei unterschiedlichen Fügepunktabständen, was zu zwei verschiedenen Längen des Wirkabstands in Bezug auf die Rotationsachse im Torsionsversuch führt. Das erste Teilziel der Untersuchung ist die Bewertung der Tragfähigkeit der Mehrfachanordnungen von Clinchpunkten unter Torsionsbeanspruchung. Ein zweites Teilziel ist die Analyse des Einflusses eines zusätzlichen Clinchpunkts, der als Drehgelenk in der Rotationsachse wirkt, auf das Tragverhalten und das Versagensverhalten der Fügeverbindung. Aus den erarbeiteten Resultaten werden Erkenntnisse zum Tragverhalten der Fügeverbindungen abgeleitet und eine Überschlagsrechnung vorgestellt, um Richtlinien zur konstruktiven Auslegung von Bauteilen aufzustellen.
Keywords: Clinchen; Mehrfachanordnung; Torsionsprüfung; Tragfähigkeit

Ultra-Low Phase Noise Frequency Synthesis Using Electro-Optic Detector-Based Comb-Microwave Synchronization - Surendranath Shroff, Vijayalakshmi; Bahmanian, Meysam; Scheytt, J. Christoph (2025 IEEE/MTT-S International Microwave Symposium - IMS 2025)

Noise Folding in Optoelectronic PLLs for Ultralow Phase Noise: Modeling and Suppression With Experimental Validation - Surendranath Shroff, Vijayalakshmi; Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)